Strategi Pemasaran UMKM “Es Teler” Berbasis Marketing Mix 7P - Ribby Fabiyan Shativa; Olivia Latuhihin (Yayasan Aya Sophia Indonesia, 2025)
Traditional beverage businesses such as Es Teler face significant challenges amid the growth of an increasingly competitive modern fresh beverage industry. Changing consumer preferences and intensifying competition require micro, small and medium enterprises to devise more structured and adaptive marketing strategies. This study aims to develop a marketing strategy for Es Teler using the 7P Marketing Mix approach, which includes product development, pricing, location selection, promotional strategies, service quality, process efficiency, and strengthening physical evidence. The analysis was conducted through the identification of target markets, consumer behaviour, and mapping of direct and indirect competitors. The results of the study show that consumers now value not only delicious taste, but also cleanliness, product appearance, ease of purchase, and promotional creativity. Based on these findings, this paper outlines short-, medium-, and long-term strategy implementation steps and establishes evaluation indicators to measure marketing effectiveness. With proper planning, Es Teler micro, small, and medium enterprises have the opportunity to increase competitiveness, expand their market, and maintain their existence amid the dynamics of the beverage industry.